SOCIAL MEDIA ADVERTISING FACTORS AND ITS IMPACT ON CONSUMER PURCHASE DECISIONS - Rajalakshmi, D; Thabassum, N. Fathima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Social media advertising gives companies the ability to connect with customers, target particular audiences, and personalize ads. It offers real-time customer feedback, enabling data-driven marketing decisions. In the digital age, this study looks at how social media marketing affects consumer purchasing decisions. This study aims to analyze the influence of factors such as brand reputation, product reviews, and visual appeal on consumer purchase decisions. The research uses a structured questionnaire and a sample size of 250 respondents from the Tirupattur district of Tamil Nadu. The findings show that a young, male-dominated population with moderate to high income levels engages with social media ads by liking or sharing them, but deeper interactions are less common. Brand reputation is the most critical factor influencing purchasing decisions in social media advertisements, followed by visual appeal and product reviews. Content quality and brand trust are less influential, suggesting that enhancing these areas can drive sales.